2001
DOI: 10.1162/089892901564289
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Processing of Social Information from Faces in Autism

Abstract: Abstract& Autism has been thought to be characterized, in part, by dysfunction in emotional and social cognition, but the pathology of the underlying processes and their neural substrates remain poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
390
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 514 publications
(413 citation statements)
references
References 40 publications
(59 reference statements)
17
390
2
4
Order By: Relevance
“…Less than a third of the AS group members recognised this mental state successfully, which supports evidence from other studies, showing specific difficulty in understanding deception (Baron-Cohen, 1992;Sodian & Frith, 1992). One study found that high-functioning adults with autism had difficulties assessing the trustworthiness and approachability of people from pictures of their faces (Adolphs et al, 2001). Their participants tended to evaluate people in the photos as being more trustworthy and approachable than controls' evaluations.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Less than a third of the AS group members recognised this mental state successfully, which supports evidence from other studies, showing specific difficulty in understanding deception (Baron-Cohen, 1992;Sodian & Frith, 1992). One study found that high-functioning adults with autism had difficulties assessing the trustworthiness and approachability of people from pictures of their faces (Adolphs et al, 2001). Their participants tended to evaluate people in the photos as being more trustworthy and approachable than controls' evaluations.…”
Section: Discussionsupporting
confidence: 77%
“…Adults with autism spectrum conditions may also not differ from typically developed controls in the ability to recognise the 6 basic emotions (Adolphs, Sears, & Piven, 2001). These groups also passed first-and second-order theory of mind tasks, which could be taken to indicate no theory of mind difficulty in autism.…”
mentioning
confidence: 99%
“…Supporting the hypothesis that amygdala dysfunction contributes to face processing abnormalities in ASD are some commonalities between ASD and patients with bilateral amygdala lesions (reviewed in [211,212]), including deficits in fear-face recognition, bias towards rating faces as more trustworthy and approachable [210], atypical patterns of face viewing [55,56] (but see [57]) and failure to attribute social intention to moving geometric shapes [213]. Other lines of evidence implicating amygdala dysfunction in ASD include evidence for amygdala neuropathology from post-mortem studies [214], and autistic-like social and emotional behavior among non-human primates with amygdala lesions early during infancy [215] (but see [216]).…”
Section: Impairments Of Facial Expression Recognition In Asdmentioning
confidence: 92%
“…For example, high functioning ASD adults were reported to rate faces as more trustworthy and approachable than did normal controls [210]. Also, Pelphrey et al (2002) found that relative to age and gender matched controls, high functioning adult males with ASD made more errors in identifying emotion expressions, being more likely to misidentify fear as anger, surprise or disgust, while identifying happiness, sadness and surprise at control levels [55].…”
Section: Impairments Of Facial Expression Recognition In Asdmentioning
confidence: 99%
“…Several brain structures and pathways have been suggested to underlie this disorder, among them the amygdala (Bachevalier, 1994;Baron-Cohen et al, 1999;Adolphs et al, 2001), which exhibits a number of abnormalities. Whereas earlier postmortem studies on autistic patients indicated an increased number of cells with reduced cell size in the cortical, medial, and central nuclei of the amygdala (Kemper and Bauman, 1998), more recent and modern stereological counts of neurons in the amygdala revealed a reduced number of neurons, particularly in the lateral nucleus (Schumann and Amaral, 2006).…”
Section: Introductionmentioning
confidence: 99%